Extravasation of Microspheres in a Rat Model of Silent Brain Infarcts. Issue 6 (June 2019) - van der Wijk, Anne-Eva; Lachkar, Nadia; de Vos, Judith; Grootemaat, Anita E.; van der Wel, Nicole N.; Hordijk, Peter L.; Bakker, Erik N.T.P.; vanBavel, Ed
Abstract : Background and Purpose—: We developed a rat model of silent brain infarcts based on microsphere infusion and investigated their impact on perfusion and tissue damage. Second, we studied the extent and mechanisms of perfusion recovery. Methods—: At day 0, 15 µm fluorescent microspheres were injected into the right common carotid artery of F344 rats. At days 1, 7, or 28, the brain was removed, cut in 100-µm cryosections, and processed for immunofluorescent staining and analysis. Results—: Injection of microspheres caused mild and transient damage to the treated hemisphere, with a decrease in perfused capillary volume at day 1, as compared with the untreated hemisphere. At day 1 but not at days 7 and 28, we observed IgG staining outside of the vessels, indicating vessel leakage. All microspheres were located inside the lumen of the vessels at day 1, whereas the vast majority (≈80%) of the microspheres were extravascular at day 7, and 100% at day 28. This was accompanied by restoration of perfused capillary volume. Conclusions—: Microspheres cause mild and transient damage, and effective extravasation mechanisms exist in the brain to clear microsized emboli from the vessels. Abstract : Supplemental Digital Content is available in the text.